Odpowiedź :
a) W(x) = x²-36
W(x) = (x-6)(x+6)
b) W(x) = 4x²+4x+1
W(x) = (2x+1)²
c) W(x)= x⁶-x²
W(x) = (x³-x)(x³+x)
d) W(x) = x³-64
W(x) = (x-4)(x²+4x+16)
Chyba tak ;))
W(x) = (x-6)(x+6)
b) W(x) = 4x²+4x+1
W(x) = (2x+1)²
c) W(x)= x⁶-x²
W(x) = (x³-x)(x³+x)
d) W(x) = x³-64
W(x) = (x-4)(x²+4x+16)
Chyba tak ;))
W(x)=(x-6)(x+6)
W(x)=(2x²+1)²
W(x)=x²(x⁴-1)=x²(x²-1)(x²+1)=x²(x-1)(x+1)(x²+1)
W(x)=(x-1)(x²+x+1) lub (x+1)(x²-x+1)= x³+64
W(x)=(2x²+1)²
W(x)=x²(x⁴-1)=x²(x²-1)(x²+1)=x²(x-1)(x+1)(x²+1)
W(x)=(x-1)(x²+x+1) lub (x+1)(x²-x+1)= x³+64